X‐ray fluorescence determination of Cs, Ba, La, Ce, Nd, and Ta concentrations in rocks of various composition. (7th March 2017) - Suvorova, Darya; Khudonogova, Elena; Revenko, Anatoly
Abstract : The technique has been developed for the quantification of small tantalum, cesium, barium, lanthanum, cerium, and neodymium concentration in rocks with X‐ray wavelength dispersive spectrometer S8 TIGER (Bruker AXS, Germany). The optimum conditions have been chosen for registration of the analyzed elements characteristic radiation and background positions. To determine the concentrations of analyzed elements accurately, the contribution of overlapping lines to the experimental intensities of the analytical lines has been taken into account. The sample of mass about 1.2 g has been pressed into pellet by the hydraulic press. Metrological studies showed that the accuracy in the determination of the concentration of analyzed elements for the developed technique meets the requirements for methods of III accuracy class. The Ta detection limits calculated for TaLβ1 ‐analytical and CsLα1 ‐analytical lines were 2.6 and 3.4 ppm, respectively. The detection limit of Ba, La, Ce, and Nd was (in ppm), respectively, 4.3, 2.7, 5.8, and 4.7. The metrological characteristics of the previously developed and adapted techniques were compared. Ta concentration in granite pegmatite samples has been quantified. The samples of the highest tantalum content have been investigated additionally by powder diffraction and X‐ray microprobe analysis. The X‐ray diffraction method turned out to be insensitive to the detection of mineral phase of tantalum niobates, while micro‐XRF allowed detecting its presence in tourmaline grains. Copyright © 2017 John Wiley & Sons, Ltd.